17-2 Variasi Penggunaan Beeswax Lip Balm Stik dari Ekstrak Kulit Nanas (Ananas comosus (L.) Merr.) - Resi Rizki Banjarani; Muhammad Arif; Nursyafni; Widiya Ismail; Najmi Hilaliyati (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2025)
Lip balm is a preparation applied to the lips to prevent dryness and chapping. Choosing the right lip balm base will significantly impact its quality and public acceptability. Beeswax has good binding properties, which help to produce a homogeneous mass. In this study, the active ingredient used was pineapple peel because it contains bromelain, which moisturizes the lips. The objectives of this study were to determine the appropriate formulation for lip balm preparations with pineapple peel extract (Ananas comosus (L.) Merr.) as the active ingredient and to determine the effect of varying beeswax base concentrations on the physical stability of lip balm preparations. The method used in this study was an experimental method to see which formulation was suitable. The study obtained a good formula with physical characteristics in accordance with SNI 16-4769-1998, including stability observation, pH measurement, homogeneity testing, irritation testing, moisture testing, and cycling test. The appropriate formula was found in formula 1 with a beeswax concentration of 1%, which produced a good color texture, aroma, adhesive power, and spreadability, a pH level suitable for the lips, no irritation, homogeneity, and stability during storage, resulting in a semi-solid and very smooth lip balm texture when used